Four-Bar Linkage Path Generation Problems Using a New TLBO and Optimum Path Repairing Technique - Seksan Winyangkul; Mahmoud Alfouneh; Suwin Sleesongsom (Biomimetics, 2026)
-value (0.0455) < α (0.05). It can be concluded that ATLBO-EFA with OPRT offers the best solution for solving the four-bar path synthesis problems.
Keywords: Advanced Multi-Objective Optimization Algorithms; Metaheuristic Optimization Algorithms Research; Advanced Optimization Algorithms Research